λ-Density Functional Valence Bond: A Valence Bond-Based Multiconfigurational Density Functional Theory With a Single Variable Hybrid Parameter - Ying, Fuming; Zhou, Chen; Zheng, Peikun; Luan, Jiamin; Su, Peifeng; Wu, Wei (Frontiers in Chemistry, 2019)
A new valence bond (VB) based multireference density functional theory (MRDFT) method, named λ-DFVB, is presented in this paper. The method follows the idea of the hybrid multi-reference density-functional method theory proposed by Toulouse et al (J. Chem. Phys., 2012, 137, 044104). λ-DFVB combines valence bond self-consistent field (VBSCF) method with KS-DFT by decomposing the electron-electron interactions with a hybrid parameter λ. Different from the Toulouse’s scheme, the hybrid parameter λ in λ-DFVB is variable, defined as a function of a multi-reference character of a molecular system. Furthermore, the EC correlation energy of a leading determinant is introduced to ensure size-consistency at the dissociation limit. Satisfactory results of test calculations, including potential energy surfaces, bond dissociation energies, reaction barriers, and singlet-triplet energy gaps, show the potential capability of λ-DFVB for molecular systems with strong correlation.